Strategies to Increase the Productivity of Tilapia Fish Cultivation as Flagship Product in Kramatjegu: Strategi Peningkatan Produktivitas Budidaya Ikan Nila Sebagai Produk Unggulan di Desa Kramatjegu - Apriliana Sari, Indah; Ayuni, Shazana Dhiya; Hudi, Lukman (Procedia of Social Sciences and Humanities, 2022)
Pandemic Covid 19 is a difficult moment for the whole of community. Where the word health and economy is experiencing a downturn that affects to the lower levels of society, not exception the people in Kramatjegu village. By the utilizing of existing land, and unused building goods they made some of fish ponds from a sheeting. With a little of cultivation knowledge they start farming close their homes. The problems emerged in the first month of cultivation started. There were a lot of Tilapia fish have died, and they had stopped their cultivation. The lack of knowledge and there are not guidance book about Tilapia maintenance, makes people solved the problem did not appropriate. Another cause of Tilapia fish have died are lack of quality water control such as pH and O2, and improper of feed techniques. Consequently, the harvest plan did not match with the time and quantity targeted. So, the solution to that problems are provide education and work instruction of Tilapia care work.